Self-reported Age of Hypertension Onset and Hypertension-Mediated Organ Damage in Middle-Aged Individuals - Karri Suvila; Elizabeth L McCabe; Joao A C Lima; Jenni Aittokallio; Yuichiro Yano; Susan Cheng; Teemu J Niiranen (OXFORD UNIV PRESS, 2022)
BackgroundObjectively defined early onset hypertension, based on repeated blood pressure measurements, is a strong risk factor for cardiovascular disease (CVD). We aimed to assess if also self-reported hypertension onset age is associated with hypertension-mediated organ damage (HMOD). Additionally, we evaluated the agreement between self-reported and objectively defined hypertension onset age.MethodsWe studied 2,649 participants (50 4 years at the time of outcome assessment, 57% women) of the Coronary Artery Risk Development in Young Adults (CARDIA) study who underwent measurements for echocardiographic left ventricular hypertrophy (LVH), left ventricular diastolic dysfunction (LVDD), coronary calcification, and albuminuria. We divided the participants into groups according to self-reported hypertension onset age (<35 years, 35-44 years, >= 45 years, and no hypertension). We used multivariable-adjusted logistic regression models to assess the relation between self-reported hypertension onset age with the presence of HMOD, with those who did not report hypertension as the referent group.ResultsCompared with individuals without self-reported hypertension, self-reported hypertension onset at <35 years was associated with LVH (odds ratio (OR), 2.38; 95% confidence interval (CI), 1.51-3.76), LVDD (OR, 2.32; 95% CI, 1.28-4.18, coronary calcification (OR, 2.87; 95% CI, 1.50-5.47), and albuminuria (OR, 1.62; 95% CI, 0.81-3.26). Self-reported hypertension onset at >= 45 years was only associated with LVDD (OR, 1.81; 95% CI, 1.06-3.08). The agreement between self-reported and objectively defined hypertension onset age groups was 78-79%.ConclusionsOur findings suggest that self-reported hypertension onset age, a pragmatically feasible assessment in clinical practice, is a reasonable method for assessing risk of HMOD and CVD.